EFEKTIVITAS PROGRAM KELUARGA HARAPAN PASKA PENERAPAN QANUN NO 11 TAHUN 2018 TENTANG LEMBAGA KEUANGAN SYARIAH DI KOTA LANGSA - anggi wahyuni (Jurnal Samudra Ekonomika, 2023)
Abstract This study aims to determine the effectiveness of the Family Hope Program (PKH) in Indonesia Langsa District, Pasha City Implementation of qanun No 11of 2018 concerning Institutions Sharia Finance. The indicators used in this study are the right indicators Bantwan target, right amount, right time and right use. Sources of data that used in this research are primary and stunder data. Collection method data obtained from observatuons, questionnaires and documentation. The data analysis method used is quantitative descriptive analysis with percentage calculation. Then the results will be interpreted on the effectiveness PKH in see from the category of very effective, effective, ineffective and very ineffective. Results research shows that the implementatation of PKH in Langsa Kota District has running very effectively from each indicator seen from the average answer respondents amounted to 84.90% with a very effective triteria.